Lateral neck dissection for the treatment of synchronous and metachronous lateral neck metastasis of N1b papillary thyroid cancer - Yun, Hyeok Jun; Lee, Jin Seok; Lee, Jun Sung; Kim, Seok Mo; Chang, Hojin; Lee, Yong Sang; Chang, Hang-Seok; Park, Cheong Soo (Frontiers in Endocrinology, 2023)
Introduction Metachronous lateral neck recurrence after thyroidectomy for N1b papillary thyroid cancer is accompanied by high morbidity and increased difficulty of reoperation. From the perspective of recurrence, the objective of this study was to compare patients who underwent metachronous lateral neck dissection (mLND) despite initial thyroidectomy and patients who underwent synchronous lateral neck dissection (sLND) for papillary thyroid cancer and analyze the risk factors for recurrence after mLND. Method This retrospective study involved 1,760 patients who underwent lateral neck dissection for papillary thyroid cancer at the Gangnam Severance Hospital, a tertiary medical center in Korea, from June 2005 to December 2016. The primary outcome was structural recurrence, and secondary outcome measures were risk factors of recurrence in the mLND group. Result A total of 1,613 patients underwent thyroidectomy and sLND at diagnosis. In 147 patients, thyroidectomy alone was performed at the time of diagnosis, and mLND was performed when recurrence to the lateral neck lymph node was confirmed. During a median follow-up of 102.1 months, 110 (6.3%) patients experienced a recurrence. There was no significant difference in the recurrence between the sLND and mLND groups (6.1% vs 8.2%, P=.32). The period from lateral neck dissection to recurrence was longer in the mLND group than in the sLND group (113.6 ± 39.4 months vs 87.0 ± 33.8 months, respectively, P<.001). Age ≥50 years (adjusted HR=5.209, 95% CI=1.359–19.964; P=.02), tumor size >1.45 cm (adjusted HR=4.022, 95% CI=1.036–15.611; P=.04), and lymph node ratio in the lateral compartment (adjusted HR=4.043, 95% CI=1.079–15.148; P=.04) were independent variables predictive of recurrence after mLND. Conclusion mLND is suitable for treating lateral neck recurrence in patients with N1b papillary thyroid cancer who previously underwent thyroidectomy. Lateral neck recurrence after treatment in patients who underwent mLND was predicted by age, tumor size, and lymph node ratio in the lateral compartment.